CYBER LAW INDONESIA,ANTARA KEBUTUHAN ATAU PELENGKAP - Sidik Sidik (LPPM Universitas Bina Sarana Informatika, 2008)
The use of internet technology affects greatly toward its users. It is seen clearly on the increasing number of internet users in big cities in Indonesia and other parts of the world. This triggers various motives of users from good to malicious attempts for crimes. Therefore, a set of identified regulation in a form of Cyber Law and its enforcement is an urgency to take action against internet abuse done by lawbreaker users.